FAKTOR-FAKTOR INTERNAL YANG MEMPENGARUHI KEBERHASILAN USAHA PEDAGANG BATIK DI PASAR KLEWER SURAKARTA - MUH. NURHADI SULISTYONO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The purpose of this study were (1) To examine the effect of a partial capital, old business, and the business location to the success of batik traders at Klewer Market. (2) To examine the effect of simultaneously between capital, old business, and the business location to the success of batik traders at Klewer Market. (3) To determine the most dominant factor to the success of batik traders at Klewer Market. Â The study was conducted on batik traders in Klewer market Surakarta. The population in this research were 105 traders taken as many as 30 traders. As for how sampling is done by means of proportional stratified random sampling. In this study, researchers used a type of quantitative data from primary sources and secondary sources. The technique of data analysis using multiple linear regression with t test, F test, determination analysis. The results of data analysis found that there are significant capital and business location to the success of batik traders at Klewer Market. While the old business do not affect the success of batik traders at Klewer Market. Capital, old business, and business locations simultaneously positive and significant impact on the success of the business of batik traders in Surakarta Klewer Market. Approximately 84.50% variable business success batik traders in Surakarta Klewer Market can be explained by the variable capital, old business, and the business location. While the remaining 15.50% is explained by other variables outside variables examined in this study.